Data center and the city : A potential for urban synergies. - Ramos Cáceres, Cristina; Sandberg, Marcus; Sotoca, Adolfo (Luleå tekniska universitet, Arkitektur och vatten, 2019)
The investment landscape for the data center (DC) industry in Europe is currently under transformation, as more DC companies are getting established in the Scandinavian countries; but still the DC surface and power capacity (m² and MW) in these regions has not yet capitalized in the same way as DC traditional locations in central Europe. Nevertheless, the renewable energy as hydropower and a favorable climate for free air cooling that are provided in the North, particularly northern Sweden, among other reasons, are increasingly attracting DC companies seeking to meet their environmental goals at the lowest cost. However, this raises questions on how the land (m²) and energy (MW) demand for new DCs can be met with equity in the local context. While some governments facilitate land management procedures to build new DC facilities and lower the energy tax in order to attract more investors, there has been little attention on how these strategies could support or hinder potential energy synergies with potential social value within the local community (e.g. reuse of DC waste-heat for urban farming). The potential transition that Sweden is facing, due to the DCphenomenon, becomes a relevant context to investigate alternatives of how to improve urban metabolism’s efficiency, in relation with an emerging energy intensive industry; The Data Center industry. The purpose of this research is to investigate how urban planning theory can assist the DC-phenomenon in transitioning towards a circular approach. ISBN för värdpublikation: 978-88-99243-93-7